STUDI PENANGANAN AIR ASAM TAMBANG DENGAN METODE AKTIF (ACTIVE TREATMENT) PADA PT. BUKIT ASAM Tbk (Studi Kasus KPL Saluran ALP IUP Tambang Air Laya) - Agus Margana Womal (Retii, 2019)
ABSTRACT Coal mining, excavation and stockpiling activities carried out by PT. Bukit Asam Tbk has the potential to produce acidic water or commonly called acid mine drainage (AAT) which does not meet environmental quality standards including pH parameters, Fe and Mn metal content to fulfill the quality standards must be processed and handled. PT. Bukit Asam Tbk in handling acid mine drainage using active treatment and passive (passive treatment). The active method is by using chemicals as neutralization pH includes quicklime, in the mining industry tohor lime is commonly used in neutralizing the acidity (pH) of acid mine drainage. The results showed that AAT prior to handling had not met environmental quality standards (BML) based on Ministerial decree of environmental number 113 of 2003 and South Sumatra governor of regulations number 8 of 2012 for pH parameters (4) Fe concentration (8.2908 mg/l) and Mn concentration (6.1295 mg/l). Whereas after handling using calcium lime has met BML set by the government based on the parameters ph (7), the concentration of Fe (0.3259), and the concentration of Mn (0.2685).Comparison of the need for the amount of lime and the volume of acid mine drainage in the KPL ALP channel is obtained if the volume of water in the KPL is 8,640,000 L/day, then the need for quicklime (1.728 Kg/day), then 6,912,000 L/day for quicklime (1.382,4 Kg/day) and the volume of water 9,504,000 L/day, the need for quicklime (1.900,8 Kg/day).Keyword : Acid mine drainage, active method, pH, Fe, Mn